Albumin-based drug delivery using cysteine 34 chemical conjugates – important considerations and requirements. (July 2017) - Caspersen, Mikael B; Kuhlmann, Matthias; Nicholls, Karl; Saxton, Malcolm J; Andersen, Birgitte; Bunting, Karen; Cameron, Jason; Howard, Kenneth A
The long blood circulation time of albumin has been clinically utilized as a half-life extension technology for improved drug performance. The availability of one free thiol for site-selective chemical conjugation offers an alternative approach to current genetic fusion and association-based products. This special report highlights important factors for successful conjugation that allows the reader to design and evaluate next-generation albumin conjugates. Albumin type, available conjugation chemistries, linker length, animal models and influence of conjugation on albumin pharmacokinetics and drug activity are discussed.